Status of the pulp and periapical disorders diagnosis teaching focused on the clinical method - Taissé Duany Mejias; José Aurelio Quiñones Díaz; Trinidad Atiés Caballero; Alexis García Somodevilla; Clotilde Mora Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: the teaching of the pulp and periapical diseases diagnosis is defined as an essential content of the teaching-learning process in the Clinical Operative subject, to fulfill the main functions declared in the professional profile of the general stomatologist training model in Cuba. Objective: to determine the current state of pulp and periapical disorders teaching diagnosis in the Stomatology career Clinical Operative subject. Methods: observational, descriptive and cross-sectional research carried out at the Cienfuegos University of Medical Sciences on a population of 8 teachers and 37 third-year students of the 2017-2018 academic year. A guide was used to directly observe how the teaching of the diagnosis of pulp and periapical diseases is carried out and a survey was applied to teachers and students with closed questions. Results:it was evidenced as a strength that education at work predominates as an organizational form and there are references to the clinical method teaching in the medical career. Limitations were found in the faculty with respect to the teaching and scientific categories and years of experience; limited use of the students characterization and their results as well as deficient application of the essential actions corresponding to the diagnostic stage of the clinical method and prevalence of the teacher authoritarian role. Conclusions: still limitations in the diagnosis of pulp and periapical diseases current teaching of the population under study.